Mathematics Anxiety and Learning Interest Among Sharia Economics Students: A Gender-Based Analysis in Indonesian Higher Education - Imrona Hayati; Suci Wulandari; Surip Stanislaus; Diah Dwi Santri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
Mathematics education in Indonesia continues to face persistent challenges, particularly concerning student anxiety and engagement. While prior studies have extensively explored the math anxiety on academic performance, investigations at the higher education level remain limited. This study explores the relationship between math anxiety and learning interest, specifically focusing on gender differences among students in the Sharia Economics Program at STAI Sangatta, East Kutai. Adopting a quantitative approach, data were collected from 72 students via a digital questionnaire comprising 30 items measuring anxiety and 15 assessing interest in mathematics, all rated on a four-point Likert scale. The Pearson correlation analysis revealed a moderate but statistically insignificant positive correlation for male students (r = 0.431), and a strong, statistically significant positive correlation for female students (r = 0.750). These findings suggest that higher anxiety levels may be linked to increased motivation to learn mathematics among female students. This perspective challenges the conventional belief that academic anxiety is solely detrimental. The study emphasizes the need for integrated strategies that address both emotional and motivational aspects of learning. It advocates for gender-sensitive teaching methods and inclusive educational practices, particularly in disciplines like Sharia Economics, where mathematical proficiency is essential for academic and professional success.